Pengaruh Kompensasi Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Pada Dinas Perdagangan Dan Perindustrian Kabupaten Jombang - Anandita, Septian Ragil; Auliya, Azizah Nur; Mahendri, Wisnu (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
In a research work has a purpose, where this study aims to determine. To determine the effect of compensation and leadership style on the performance of the employees of the Department of Trade and Industry in Jombang, this research was carried out at the Department of Trade and Industry of Jombang Regency, with a population and sample of 65 employees of the Department of Trade and Industry. industry in Jombang Regency, the research instrument is a questionnaire/questionnaire with a Likert scale model. The requirements test is carried out by testing the validity and reliability tests as well as the classical assumption test. The data analysis technique used is multiple linear regression analysis technique at a significance level of = 0.05. In partial hypothesis testing, it has been proven that there is an influence between leadership style on employee performance with a significant value level of 0.025 <0.05, thus Ha is rejected and Ho is accepted, then in partial hypothesis testing has proven that there is an influence between compensation on employee performance with a significant value level. of 0.001 < 0.05, thus Ha is rejected and Ho is accepted, then the F test proves that the two independent variables have a simultaneous effect on the dependent variable with a significant value of 0.000 < 0.05 which is declared to have a positive and significant effect.